Overcoming child malnutrition in developing countries: past achievements and future choices - Smith, Lisa C.; Haddad, Lawrence J. (International Food Policy Research Institute, 2000)
About 167 million children under five years of age —almost one-third of the developing world’s children —are malnourished. If they survive childhood, many of these children will suffer from poorer cognitive development and lower productivity. As adults, their ability to assure good nutrition for their children could be compromised, perpetuating a vicious cycle. What will it take to eradicate child malnutrition in developing countries? As Lisa Smith and Lawrence Haddad point out in this 2020 Vision discussion paper, Overcoming Child Malnutrition in Developing Countries: Past Achievements and Future Choices, we must first understand the causes of malnutrition and delineate which are the most important before we can identify and act upon those areas of intervention that will be most successful in reducing malnutrition. Toward that end, their path-breaking research identifies and assesses the contribution of each key determinant to reductions in child malnutrition over the past quarter century. The most startling and important finding is that improvements in women’s education have contributed by far the most, accounting for 43 percent of the reduction in child malnutrition between 1970 and 1995, while improvements in per capita food availability con tributed about 26 percent. In a signal service to policymakers, Smith and Haddad also evaluate the potential of these factors to further reduce malnutrition durng the next two decades to 2020 and lay out the key policy priorities for each major developing region. By shedding light on which areas of intervention will be most successful in overcoming child malnutrition in developing countries, this research will contribute to realizing the 2020 Vision of a world where hunger and malnutrition are absent."" (Forward by Per Pinstrup-Andersen)